An Analysis of the Determinants of the Multiplex Urban Networks in the Yangtze River Delta. (3rd March 2019) - Zhang, Weiyang; Derudder, Ben; Wang, Jianghao; Witlox, Frank
Abstract: This paper examines the determinants of the spatial and topological structure of three types of urban networks within the Yangtze River Delta. These networks consist of transport infrastructure links, business interactions in producer services firms, and leisure mobility. The influence of distance, size, administrative borders, landform contiguity, cultural affinities, economic alliances and administrative rank are examined. We position our findings as an empirical elaboration of the formation of multiplex urban networks. Our results show that in spite of significant correlations between all of these explanatory factors and the three urban networks, only some factors affect each of the three networks. More specifically, the business network has a weak dependence on distance and cultural affinities; intercity mobility is closely related to the size of cities' populations and distance; and landform patterns remain a fundamental basis for intercity transport linkages. Our results highlight China's hierarchical‐administrative specifics in the shaping of urban networks.